(untitled) (Asian Education Studies, 2018)
This collective case study provides insights into the ways that superintendents lead learning in six highly successful and learning focused school districts. Themes from our cross-case analysis generated five major assertions offered as lessons for superintendency teams: framing leadership research in action, leading learning through superintendency teams, building purposeful professional relationships, accessing external and internal expertise, and travelling the pathways of collaborative leadership learning. Evidence was collected through 23 focus groups and 16 individual interviews. In total, 114 educational leaders participated: 53 principals, 33 central office leaders, and 28 superintendency team leaders. Data from documents, artifacts, field notes, and an online survey were also gathered in pursuit of transferable insights for district leaders practicing in other settings.